Experimental Analysis of Automatic Cooling Device Using Ferrofluid - Singh, Sahib; Garg, Harry (Asian Review of Mechanical Engineering, 2016)
Heat is an inevitable byproduct of all the electronic devices and a substantial amount of power is lost in cooling of these devices. The automatic cooling device discussed in this paper utilizes the waste heat and in the presence of magnetic field can be used for cooling applications. This cooling device converts a part of thermal energy into kinetic energy of the fluid does not require any pump for the fluid flow. If a permanent magnet is used, no external power is required for fluid flow.